Economic Development in South and East Asia: empirical examination of East Asian development model - Prakash Kumar Shrestha (Asia-Pacific Development Journal, 2014)
In this paper, a comparison is made of the level of economic development between South Asia and East Asia, and the East Asian Development Model (EADM) is analysed as well as empirically examined. Several development indicators reveal that South Asia in general is far behind East Asian countries where some distinctive features of the development process followed in the past were the developmental role of the state, high investment, emphasis on the manufacturing sector, export-led growth and a focus on infrastructure and human capital. Based on an empirical examination, which supports these facts, policymakers in South Asia should take heed of some of these features despite changing circumstances.